Performance Testing and Preventive Maintenance of Roller Bending Machine Using the ISMO Method - Adhan Efendi; Yohanes Sinung Nugroho (Universitas Sultan Ageng Tirtayasa, 2022)
This study aimed to perform performance testing and make a preventive maintenance plan on the roller bending machine with inspection, small-repair, medium repair, and overhaul (ISMO) methods. The preventive maintenance time of the roller bending machine run with daily and monthly types of maintenance. The results showed that the performance and calculations to determine the radius of the rolling results with the digital calculation method through the machine test application worked optimally. Monthly and daily routine preventive maintenance was accomplished using the ISMO method. The total time required for the roller bending machine prevention machine maintenance is 800 minutes per month. The breakdown includes 180 minutes for inspection, 80 minutes for minor repair, and 540 minutes for moderate repair.